Community Awareness of High-Tech Crime Prevention in the Digital Transformation Context in Ho Chi Minh City: A Basis for Community-Based Solutions and Policy Implications - Phan Nhan Trung (PT. Riset Press International, 2026)
Amid Vietnam's accelerating digital transformation, high-tech crime has escalated dramatically, with estimated losses of VND 18,900 billion (approximately USD 756 million) in 2024 alone. While the victimization rate declined from 0.45% to 0.18% in 2025, attack methods are becoming increasingly sophisticated through Deepfake technology, AI-powered social engineering, and mobile malware. This study conducted a community needs assessment to evaluate the current state of awareness and preventive behaviors regarding high-tech crime among residents in four areas of Ho Chi Minh City, thereby providing an evidence base for community-based solutions and policy implications. A cross-sectional quantitative survey using a 5-point Likert scale questionnaire was administered to 347 residents. Data were analyzed using SPSS 26.0, encompassing descriptive statistics, Cronbach's Alpha reliability testing, Exploratory Factor Analysis (EFA), Pearson correlation analysis, multiple linear regression, Independent Samples T-test, and One-way ANOVA. Community awareness was at a moderate level (M = 3.41 on a 5-point scale). Self-efficacy (SE), program quality (PQ), perceived threat awareness (PTA), and digital literacy (DL) collectively explained 62.1% of the variance in digital protective behavior (DPB). Self-efficacy exerted the strongest influence (beta = 0.312, p < 0.001), followed by program quality (beta = 0.274, p < 0.001). ANOVA revealed significant age-group differences (F = 8.743, p < 0.001), with residents over 55 scoring lowest (M = 2.87). Based on these findings, the study proposes targeted community interventions prioritizing vulnerable groups, enhanced digital safety outreach through social media platforms, and a community-based early warning network. Policy implications include integrating digital safety education into the municipal digital transformation roadmap and allocating dedicated budgets for ward-level awareness programs. The study contributes to SDG 16 (Peace, Justice and Strong Institutions) and SDG 4 (Quality Education).